Drivers and pressures – Untangling the terms commonly used in marine science and policy. (1st October 2016) - Oesterwind, Daniel; Rau, Andrea; Zaiko, Anastasija
Abstract: In the marine sciences an increasing number of studies on environmental changes, their causes, and environmental assessments emerged in recent years. Often authors use non-uniform and inconsistent definitions of key terms like driver, threats, pressures etc. Although all of these studies clearly define causal dependencies between the interacting socio-economic and environmental systems in an understandable way, still an overall imprecise wording could induce misunderstanding at higher policy levels when it comes to integrated ecosystems assessments. Therefore we recommend using unified definitions for a better communication between science and management within national, regional and international environmental policies, for example the European Marine Strategy Framework Directive (MSFD). With this article we provide definitions compatible with the driver-pressure-state-impact-response (DPSIR) approach. Although most examples are MSFD related and thus have a marine focus the definitions are intended to be equally applicable for other systems and are usable world-wide. We suggest sticking to these definitions for an easy and simplified knowledge transfer from science to management, since DPSIR model is already accepted as a helpful tool for structuring and communicating ecosystem analyses. Highlights: Authors use inconsistent definitions of key terms like driver and pressure. An imprecise wording could induce misunderstanding between science and policy. We provide definitions of key terms compatible with the DPSIR approach.